Analisis Perilaku Konsumen Online Aplikasi Dana Menggunakan Model Intention, Adoption, dan Continuance - Kusumah, Salma Febi Niti; Narulita, Alyana; Yusuf, Abdul (Universitas Proklamasi 45, 2023)
The era of globalization is demonstrated by technology that is developing very rapidly. Almost all sectors of life adopt technology in their operations. No exception in the financial sector, people need a payment method that is efficient, fast and safe. One example of financial technology that is widely used by Indonesian people for daily transactions is DANA, a form of digital wallet service. Digital wallets allow users to make electronic transactions without using physical cards or cash. This article aims to determine the factors that encourage users to use the DANA application repeatedly by analyzing online consumer behavior variables which include perceptions of service quality, perceptions of ease of use, and perceptions of usefulness which influence their satisfaction, as well as the influence of satisfaction on sustainable use intentions are based on the intention, adoption and continuance models. The sample used in this research was 100 DANA users who live in West Java Province. This sample was determined using the convenience sampling method and collected data through distributing online questionnaires. The results of this study found that there was a significant influence of perceived service quality and perceived convenience on satisfaction, while perceived usefulness did not have a significant influence on satisfaction. This research also found that there is a significant influence of satisfaction on the intention using it continually.